Hermann Oberth at the University of Cluj. A Necessary Clarification - GHITTA, Ovidiu (Studia Universitatis Babeș-Bolyai Historia, 2025)
The present article identifies and analyses the information concerning Hermann Oberth as a student, preserved in the archives of the former Faculty of Sciences of the University of Cluj. It brings to light a series of previously unknown details regarding his enrolment in October 1922 and the formal completion of his academic record in April 1923. These documents show that the goal pursued by the future scientist was to obtain a graduation certificate and to take the capacity examination required to obtain a teaching diploma in secondary education. Thus, he followed the course of study prescribed by the Hungarian Law of Education of 1883, which was still accepted by the newly established Romanian university authorities in Cluj, in order to settle the status of the students enrolled before the war or immediately after its end. Taking this procedural detail into account ultimately leads to abandoning a notion that has circulated for several decades, namely that, in Cluj, Oberth completed a degree examination comparable to today’s system, based on the defence of a thesis. Rezumat: Articolul semnalează și analizează informațiile despre studentul Hermann Oberth păstrate în arhiva fostei Facultăți de Științe a Universității din Cluj. Sunt detalii inedite, referitoare la înmatricularea lui Oberth, în octombrie 1922, și, respectiv, la încheierea situației sale școlare, în aprilie 1923. Din ele reiese că obiectivul avut în vedere de viitorul om de știință a fost obținerea certificatului de absolvent și prezentarea la examenul de capacitate (de obținere a diplomei de profesor în învățământul secundar). El a urmat astfel traseul prescris de legea învățământului din Ungaria, din 1883, acceptată încă de noile autorități universitare de la Cluj, românești, pentru rezolvarea situației studenților înscriși înainte de război sau imediat după încheierea acestuia. Luarea în considerare a acestui amănunt procedural impune renunțarea la ideea aflată în circulație de câteva decenii, că Oberth ar fi dat la Cluj, ca în zilele noastre, un examen de licență bazat pe susținerea unei teze. Cuvinte-cheie: Hermann Oberth, Universitatea din Cluj, anul universitar 1922-1923, certificat de absolvire, examen de capacitate.